Coincident Activation of Glutamate Receptors Enhances GABAA Receptor-Induced Ionic Plasticity of the Intracellular Cl−-Concentration in Dissociated Neuronal Cultures - Halbhuber, Lisa; Achtner, Cécilia; Luhmann, Heiko J.; Sinning, Anne; Kilb, Werner (Frontiers in Cellular Neuroscience, 2019)
Abstract Massive activation of GABA(A) receptors during pathophysiological activity induces an increase in the intracellular Cl- -concentration ([Cl-]i), which is sufficient to render GABAergic responses excitatory. However, to which extend physiological levels of GABAergic activity can influence [Cl-]i is not known. Aim of the present study is to reveal whether moderate activation of GABAA receptors mediates functionally relevant [Cl-]i changes and whether these changes can be augmented by coincident glutamatergic activity. To address these questions we used whole-cell patch-clamp recordings from cultured cortical neurons (at DIV 6-22) to determine changes in the GABA reversal potential (EGABA) induced by short bursts of GABAergic and/or synchronized glutamatergic stimulation. These experiments revealed that pressure-application of 10 short muscimol pulses at 10 Hz induced voltage-dependent [Cl-]i changes. Under current-clamp conditions this muscimol burst induced a [Cl-]i increase of 3.1 ± 0.4 mM (n=27), which was significantly enhanced to 4.6 ± 0.5 mM (n=27) when glutamate was applied synchronously with the muscimol pulses. The muscimol-induced [Cl-]i increase significantly attenuated the inhibitory effect of GABA, as determined by the GABAergic rheobase shift. The synchronous coapplication of glutamate pulses had no additional effect on the attenuation of GABAergic inhibition, despite the larger [Cl-]i transients under this conditions. In summary, these results indicate that moderate GABAergic activity can induce functionally relevant [Cl-]i transients, which were enhanced by coincident glutamate pulses. This ionic plasticity of [Cl-]i may contribute to short-term plasticity of the GABAergic system.